Learning journeys – student learning development in the first years of a medical degree: an analysis of student conversations - Gilbert, Kerry G. (Frontiers in Sociology, 2023)
Students starting medical school generally come from a learning background that expects them to learn content, which is reproduced to pass an exam. As a part of their learning development, they must adapt and become self-motivated learners who can determine the underlying principles or concepts and use these to problem solve in the uncertainty of reallife clinical practice. Whilst much has been written about designing curricula to promote learning development, there is no one-size fits all approach to facilitating this type of learning, thus an analysis of what helps and hinders learning development is indicated.Student pairs in Y2 and Y3 of an undergraduate Bachelor of Medicine, Bachelor of Surgery (BMBS) programme of a South-West UK medical school, were asked to audio record a conversation about their learning through a facilitated problem-based learning approach during the BMBS course so far. They were provided with a brief to aid them in their discussion in the style of the outside broadcast method of BBC Radio 4s listening project.Using this method, the conversation was unfacilitated and allowed to take its natural course.Conversations were transcribed and coded to determine emerging themes with respect to the developing understanding of the students about what and how they were learning.Four student pairs volunteered for the project one from Y2 and three from Y3. Five key themes were identified including: from 'learning it all, to structured learning'; 'developing understanding and the spiral curriculum'; 'working alone versus working with others'; 'integrated learning and understanding context' and 'assessment and resources.' Narrative analysis within these themes suggested that over the course of the first two to three years of study, participants developed a better understanding of how best to learn, although there were differences in both time and order that participants reached a point where learning felt more natural to them.Analysis of the data suggested that students develop independently towards being selfmotivated lifelong learners. There were several key aspects of curriculum design that could be used to facilitate this development, which could easily be incorporated into developing or creating problem-/ enquiry-based curricula.